Revolutionizing bone defect healing: the power of mesenchymal stem cells as seeds - Zhang, Yueyao; Fan, Mengke; Zhang, Yingze (Frontiers in Bioengineering and Biotechnology, 2024)
Bone defects can arise from trauma or pathological factors, resulting in compromised bone integrity and the loss or absence of bone tissue. As we are all aware, repairing bone defects is a core problem in bone tissue engineering. While minor bone defects can self-repair if the periosteum remains intact and normal osteogenesis occurs, significant defects or conditions such as congenital osteogenesis imperfecta present substantial challenges to self-healing. As research on mesenchymal stem cell (MSC) advances, new fields of application have emerged; however, their application in orthopedics remains one of the most established and clinically valuable directions. This review aims to provide a comprehensive overview of the research progress regarding MSCs in the treatment of diverse bone defects. MSCs, as multipotent stem cells, offer significant advantages due to their immunomodulatory properties and ability to undergo osteogenic differentiation. The review will encompass the characteristics of MSCs within the osteogenic microenvironment and summarize the research progress of MSCs in different types of bone defects, ranging from their fundamental characteristics and animal studies to clinical applications.